Blue sclerae and their association with glaucoma (a review and case report) - T.A. Beletskaya; E.V. Kozina; D.V. Dmitrenko; Yu.I. Gavrilova (РМЖ "Клиническая офтальмология")
T.A. Beletskaya1,2, E.V. Kozina1, D.V. Dmitrenko1, Yu.I. Gavrilova2 1Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation 2Prof. P.G. Makarov Krasnoyarsk Regional Ophthalmological Clinical Hospital, Krasnoyarsk, Russian Federation This paper reviews the key risk factors and clinical manifestations of blue sclerae, which include a large group of diseases of various origins. Generally, this syndrome is genetically determined and is a constant phenotypic sign of osteogenesis imperfecta. In addition to the classic triad of blue sclera, brittle bones, and hearing loss, many authors refer glaucoma to as an ocular manifestation of brittle bone disease in addition to thin cornea and low corneoscleral rigidity. The combination of osteogenesis imperfecta type 1 and primary open-angle glaucoma is a novel phenotypic association. The most effective way of controlling intraocular pressure (IOP) in this condition is surgical intervention. Case report of a combination of glaucoma and syndromic connective tissue disease that appeared 15 years after the first visit to an ophthalmologist for recurrent ocular hypertension is presented. Selective laser trabeculoplasty and a fixed-dose combination of 0.3% bimatoprost and 0.5% timolol provided normal IOP levels. Ultrathin corneas and systemic hypotension do not rule out the need for further surgery. Keywords: blue sclera, glaucoma, osteogenesis imperfecta, corneal thickness. For citation: Beletskaya T.A., Kozina E.V., Dmitrenko D.V., Gavrilova Yu.I. Blue sclerae and their association with glaucoma (a review and case report). Russian Journal of Clinical Ophthalmology. 2023;23(4):225–230 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-9.